Effects of Tooth Brushing on Surface Roughness and Weight Loss in Fissure Sealants with Different Filler Ratios - Ebru Hazar Bodrumlu (Annals of Abbasi Shaheed Hospital and Karachi Medical & Dental College)
Objective: The aim of this study was to evaluate the effect of tooth brushing on weight loss and surface roughness changes in fissure sealants with different filling ratios. Methods: A total of 80 samples, 20 in each, were prepared from fissure sealants containing 4 different fillers (0%, 30%, 50%, 70.2). Twenty disc-shaped samples (2 mm thick and 7 mm wide) were made from each fissure sealant using molds. Samples that were found not to be of adequate size or unsuitable for measurement were excluded from the study. After preparing samples, the initial weight measurements, and surface roughness measurements using a surface profilometer were taken. The samples underwent tooth brushing by a toothbrushing simulator. At the end of the 5,000th, 10,000th, and 20,000th cycles, weight measurements and surface roughness values were recorded. The statistical analysis was conducted using a series of tests, including the paired sample t-test, Tukey’s test, and the independent sample t-test. Results: The surface roughness values of all materials gradually decreased over the course of 2 years of tooth brushing. Samples without filler had the lowest roughness before brushing. After 24 months of brushing, samples without filler exhibited the least roughness. When evaluating weightloss the least amount of loss was observed in samples with 70.2% filler. Conclusion: The initial surface roughness values of fissure sealants are not optimal. The sealant with the highest filler content demonstrated greater resistance to material loss, while the sealant without filler exhibited superior surface properties when subjected to tooth brushing.